Paved Squares in Northern Italy Fora (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2015)
The paved squares in Roman fora of Cisalpine Gaul have been frequently neglected by scientific literature. This work is the attempt to fill the gap and to focus on such an important urban zone: it analyzes the different stone materials (marble, limestone, trachyte, sandstone and cobbles) and distinguishes between local and imported lithotypes. Thanks to recent excavations and old data, the paper considers the chronological diffusion in the towns and the general organization of the platea, whose building was sometimes guaranteed by wealthy citizens.
Keywords: Cisalpine Gaul; forum; limestone; euergetism; square; lithotypes